Model matematik hubungan variabel iklim dan produksi padi gogo studi kasus di Gunung Kidul (Mathematical model on climatic variables and rice yield relationshps : case study in gunung kidul) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
The study was conducted in Playen, Gunung Kidul District, Yogyakarta Province. The daily climatic data gathered including rainfall, sunshine duration, and relative humidity. These data was analysed by taking into account the average 5 (five) days climatic data. The first mathematical model developed by Fisher that relates climatic data to the yield of the crops was used in this study by transferring the model into the polynomial orthogonal equation. The results indicated that the only rainfall model is significant during the study. Meanwhile, the model of sunshine duration and relative humidity are not significant. The availability of rainfall during the growing period of upland rice in Playen, Gunung Kidul is more than enough for the plantation of rice.